Effect of preservation at refrigeration temperature on bacterial load and quality of buck semen - SIMON, LIZ; VIJAYAKUMARAN, V (The Indian Journal of Animal Reproduction, 2003)
The bacterial load in buck semen preserved under refrigeration temperature(8-12°C) was assessed by Pour Plate Method. The mean bacterial load showed an increasing trend from zero to 48 hours of preservation. However, there was no significant correlation between the bacterial load-and semen quality.